Music Matters: The Role of Background Music in Improving Students’ Attention and Learning Outcomes - Ázmi, Muhammad Tamim Faruq Bin Khairul; Kian, Neo Tse-; Rashid, Fajrul Norman (International Journal of Membrane Science and Technology, 2023)
This paper investigates the impact of background music on students’ cognitive performance in the classroom environment, aiming to enhance attention and improve learning outcomes. The study conducted an experiment with 100 design students from MMU, randomly dividing them into treatment and control groups. The treatment group listened to background music genres such as Lo-fi and modern classical remix, while the control group experienced silence. The effects of background music on cognitive performance were analyzed and compared. The comprehensive literature review highlights the potential of background music to positively influence cognitive functioning and learning outcomes in specific contexts. The study employed a mixed-method research design, combining qualitative data from online open-ended question surveys and quantitative data from Likert scale questionnaires. The experiment utilized pre- test and post-test measurements, with participants allocated to controlled and treatment groups using a random sampling technique. Positive findings emerged from the analysis, indicating significant improvements in attention, concentration, focus, motivation, memory, and mood among students exposed to background music. However, the study acknowledges limitations such as the small sample size and specific research context, calling for further studies with larger and more diverse samples to enhance generalizability. These findings emphasize the potential of background music to positively impact cognitive performance and contribute to enhancing students’ learning experiences.